UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI DI SMP NEGERI 1 KUBU KABUPATEN ROKAN HILIR - Karsono ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on observations while at SMPN 1 Kubu Rokan Hilir, discovered the phenomenonamong others: (a) the majority of teachers who often do not come on time even did not comefor no apparent reason; (B) the majority of teachers who often leave the office during workinghours; and (c) the tasks and activities provided by the principal to the teachers not run asexpected, especially when the task outside the official school hours, many of the teachers werenot prepared for the learning tools they should have. Remedial and enrichment programs notrunning as it should, so that learning becomes less than the maximum. This study aims toimprove the performance of teachers through supervision. This type of research is actionresearch school (PTS) located at SMPN 1 Kubu Rokan Hilir, aimed at teachers. The mainreason is of the observations and information from the teacher, that teacher performance isstill relatively lacking. Place of research is in SMPN 1 Kubu Rokan Hilir. When the study wasconducted in February 2015. The number of samples set out in this study were 20 teachers.From the description of data processing and discussion it was concluded that teacherperformance is obtained in the first cycle of 57% with good enough category and the secondcycle increased to 80% in both categories. This means that the supervision activities canimprove the performance of teachers in SMPN 1 Kubu Rokan Hilir is successful.